1999
DOI: 10.1007/bf02358402
|View full text |Cite
|
Sign up to set email alerts
|

Mutation breeding for yield andPhytophthora infestans (Mont.) de Bary foliar resistance in potato (Solanum tuberosum L. cv. Golden Wonder) using computerized image analysis in selection

Abstract: SummaryUsing visual selection for off-types and image analysis to select against maturation mutants, a line combining improved late blight resistance and yield was isolated in an in vitro mutagenesis programme from a population of 2101 putative mutants. The adventitious regener.ants from mutagenesis treatment, including spontaneous mutants (somaclonal variants), were subjected to serial subculture of the apical bud in vitro and two cycles of apical cuttings in vivo to breakdown chimeras. The selected line was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 11 publications
0
8
0
1
Order By: Relevance
“…These methods induce point mutations, deletions, or insertions, respectively and have been useful in breeding for biotic (Bhagwat & Duncan, 1998;Kowalski & Cassells, 1999) and abiotic (Fuller & Eed, 2003;Khan et al, 2001) stress in non-legume crops. In legumes most effort has occurred with nitrogen fixation (Sagan et al, 1994), and mutants with resistance or tolerance to stresses have not been described.…”
Section: Somaclonal Variation and In Vitro Mutagenesismentioning
confidence: 99%
“…These methods induce point mutations, deletions, or insertions, respectively and have been useful in breeding for biotic (Bhagwat & Duncan, 1998;Kowalski & Cassells, 1999) and abiotic (Fuller & Eed, 2003;Khan et al, 2001) stress in non-legume crops. In legumes most effort has occurred with nitrogen fixation (Sagan et al, 1994), and mutants with resistance or tolerance to stresses have not been described.…”
Section: Somaclonal Variation and In Vitro Mutagenesismentioning
confidence: 99%
“…may contribute to producing an addedvalue micropropagation product. Here and previously (Cassells & Sen, 1995;Fitzgerald, 1996;Kowalski & Cassells, 1999), it has been shown that ontogenetic (developmental) variation within the potato plant and between or within populations can be detected by differences in leaf parameter means, or by the presence of statistical outliers in the population. Here, leaf parameters have been shown to be related with crop maturation and can be used to compare the relative maturity of different populations.…”
Section: Discussionmentioning
confidence: 90%
“…Epigenetic or non-heritable variation may also be associated with pleiotropic changes in disease susceptibility (Cassells et al, 1993;Cassells & Sen, 1996). Differences in developmental maturity (ontogenetic differences) between individuals within and between potato populations, can be detected by quantifying changes in leaf morphology using computerised image analysis (Cassells et al, 1991;Cassells & Sen, 1996;Cassells et al, 1997;Kowalski & Cassells, 1999). Here, the application of computerised image analysis to potato microplants is investigated with reference to the characterisation of ontogenetic or developmental variation.…”
Section: Introductionmentioning
confidence: 98%
“…It is assumed in the latter cases that retention of the characteristics of the parent genotype is required, that is, that the mutants be near-isogenic with the parent, as in a flower color series. polyploids and gross aneuploids using flow cytometry, and morphological aberrants using image analysis, and (v) select for near-isogenicity using computerized image analysis (Kowalski and Cassells, 1999). use of bud irradiation (Sonnino et al, 1986); (ii) facilitate chimeral breakdown, e.g.…”
Section: Mutant Selectionmentioning
confidence: 99%
“…use of bud irradiation (Sonnino et al, 1986); (ii) facilitate chimeral breakdown, e.g. 4; Kowalski and Cassells, 1999). select for resistance to fungal toxins; (iv) select against gross aberrants, e.g.…”
Section: Mutant Selectionmentioning
confidence: 99%